Modulation of Arterial Stiffness Gradient by Acute Administration of Nitroglycerin - Fortier, Catherine; Garneau, Charles-Antoine; Paré, Mathilde; Obeid, Hasan; Côté, Nadège; Duval, Karine; Goupil, Rémi; Agharazii, Mohsen (Frontiers in Physiology, 2021)
ABSTRACT Background: Physiologically, the aorta is less stiff than peripheral conductive arteries, creating an arterial stiffness gradient, protecting microcirculation from a high pulsatile pressure. However, the pharmacological manipulation of arterial stiffness gradient has not been thoroughly investigated. We hypothesized that acute administration of nitroglycerin (NTG), may alter the arterial stiffness gradient through a more significant effect on the regional stiffness of medium-sized muscular arteries, as measured by pulse wave velocity (PWV). The aim of this study was to examine the differential impact of NTG on regional stiffness, and arterial stiffness gradient as measured by the aortic-brachial PWV ratio (AB-PWV ratio) and aortic-femoral PWV ratio (AF-PWV ratio). Methods: In 93 subjects (age: 61 years, men: 67%, chronic kidney disease (CKD): 41%), aortic, brachial and femoral stiffnesses were determined by carotid-femoral (cf-PWV), carotid-radial (cr-PWV) and femoral-dorsalis pedis artery (fp-PWV) PWVs, respectively. The measurements were repeated 5 minutes after the administration of NTG (0.4 mg s.l.). The AB-PWV and AF-PWV ratios were obtained by dividing cf-PWV by cr-PWV or fp-PWV respectively. Central pulse wave profile was determined by radial artery tonometry through the generalized transfer function. Results: At baseline, cf-PWV, cr-PWV and fp-PWV were respectively 12.12 ± 3.36 m/s, 9.51 ± 1.81 m/s and 9.71 ± 1.89 m/s. After the administration of NTG, there was a significant reduction in cr-PWV of 0.86 ± 1.27 m/s (p<0.001) and fp-PWV of 1.12 ± 1.74 m/s (p<0.001), without any significant changes in cf-PWV (p=0.928), leading to a significant increase in the AB-PWV ratio (1.30 ± 0.39 vs 1.42 ± 0.46; p=0.001) and AF-PWV ratio (1.38 ± 0.47 vs 1.56 ± 0.53; p=0.001). There was a significant correlation between changes in AF-PWV ratio and changes in timing of wave reflection (r=0.289; p=0.042) and the amplitude of the heart rate- adjusted augmented pressure (r=-0.467; p<0.001). Conclusion: This study shows that acute administration of NTG reduces PWV of muscular arteries (brachial and femoral) without modifying aortic PWV. This results in an unfavorable profile of aortic-brachial and aortic-femoral PWV ratios, which could lead to higher pulse pressure transmission into the microcirculation.